Review of leadership theories and management performance in organizations - Sakiru, Oladipo Kolapo; Othman, Jamilah; Ismail, Azahari; D`Silva, Jeffrey Lawrence; Kareem, Salami Dada (Medwell Journals, 2014)
Better understanding need to be developed on leadership theories and management performance in organization. The main aim of this study is to identify best styles of leadership that can raise management performance in an organization. Data for this current study were obtained from previous literature on leadership theories and management performance in organizations. From the literature review of previous studies, it was concluded that for better management performance in organizations, transformational leadership styles is highly needed because many literature are in support of this leadership style.